A phase 2 study of sorafenib combined with conventional therapies in refractory central nervous system leukemia. Issue 11 (22nd March 2022) - Chen, Xiaoxia; Huang, Junwei; Xu, Na; Fan, Zhiping; Nie, Danian; Huang, Fen; Sun, Qixin; Zhang, Xinyou; Liang, Xinquan; Shi, Pengcheng; Wang, Zhixiang; Liu, Hui; et al.
Abstract : Background: Patients with refractory central nervous system leukemia (CNSL) have a dismal prognosis and lack effective therapy. Case reports have shown that sorafenib is effective against brain metastases, including leukemia. Methods: To explore the efficacy of sorafenib combined with conventional therapies for refractory CNSL, a phase 2 study was conducted. The primary end point was the complete remission rate (CRR) within 8 weeks of treatment. Secondary end points included the overall response rate (ORR), event‐free survival (EFS), overall survival (OS), and adverse events (AEs). Results: Twenty‐six patients with refractory CNSL were enrolled; they included 17 with isolated CNSL, 7 with hematological relapse, and 2 with another extramedullary relapse. After 8 weeks of treatment, 21 patients achieved complete remission, 2 achieved partial remission, and 3 achieved no remission for a CRR of 80.8% (95% CI, 62.1%‐91.5%) and an ORR of 88.5% (95% CI, 71.0%‐96.0%). Twenty patients survived, and 6 died. The 2‐year EFS and OS rates were 75.0% (95% CI, 54.5%‐88.3%) and 76.9% (95% CI, 54.2%‐90.4%), respectively. Six patients experienced grade 3 or 4 treatment‐related AEs, including moderate chronic graft‐vs‐host disease (n = 3), grade 3 or 4 acute graft‐vs‐host disease (n = 2), and grade 3 skin rash (n = 1). No treatment‐related deaths occurred during the therapy of refractory CNSL. Conclusions: Sorafenib combined with conventional therapies is effective and safe for refractory CNSL. Lay Summary: Sorafenib combined with conventional therapies is effective and safe for refractory central nervous system leukemia. Abstract : Sorafenib combined with conventional therapies is effective and safe for refractory central nervous system leukemia.